A midrange theory of local cross-sector action based on the actor-network theory - Angèle Bilodeau; Catherine Chabot; Nadine Martin; Mélissa Di Sante; Laurence Bertrand; Louise Potvin (Elsevier, 2022)
Given the value of cross-sector collaborations in solving complex societal problems, experts are now recommending that research focus on documenting process-effect linkages. This paper proposes a validated midrange theory on the process-effect links of local cross-sector action on urban living conditions. The theory expands from an initial prospective study showing that changes were produced by sequences of a limited number (n ​= ​12) of transitional outcomes (TOs), derived from the analysis of empirical material informed by the Actor-Network Theory (ANT), that mark the progression of cross-sector processes toward their effects. This retrospective longitudinal multiple case (eight cases) study was conducted, using primarily case documents and additional interviews with actors involved, aimed at validating/expanding the transitional outcomes, and further anchoring them in ANT. The results confirm and enhance the inventory of TOs, reinforce their definitions, and solidify the midrange theory. This article presents the finalized inventory of TOs anchoring them both in the empirical observations from case studies and in their theoretical foundations drawn from ANT.